Stochastic leadtimes in a one-warehouse, N-retailer inventory system with the warehouse actually carrying stock. (10th April 2010) - Solis, Adriano O.; Schmidt, Charles P.
We previously investigated, analytically, effects of introducing stochastic leadtimes between the warehouse and retail sites in a multi-echelon model with deterministic leadtimes when the warehouse does not carry stock. In the current study, the warehouse does carry stock, making the model mathematically intractable. A heuristic involving simulation experiments is devised, taking off from deterministic leadtime model solutions. The resulting average system inventory is equal or very close to the optimal level. Our study suggests that the optimal solution to the deterministic leadtime case provides an appropriate starting point in searching, using simulation, for a solution in the stochastic leadtime case.